Android-Based Attendance Application at PT. Solusi Hidup Mandiri (SHM) - Fakhri, Raja Muh.; Abduh, Hisma; Muhallim, Muhlis (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
This research aims to design and build an Android-based attendance application. The research method used is a qualitative method. The data collection methods in this research are (1) data documentation, (2) observation, (3) interviews, and (4) questionnaires. In this research, the system development method used is a prototype with the system design using UML (Unified Modeling Language) which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. The software used in designing and implementing the system uses XAMPP as a web server, MySQL as a database, Visual Studio Code as a web design editor and Android Studio as an Android application design editor. The Android-based attendance application includes attendance, absence, absence history, and permit applications. The score obtained from the usability testing results is 93% and is in the